The Elasticity of Substitution and Endogenous Growth - LEUNG, Hing-Man (Institutional Knowledge at Singapore Management University, 2003)
The endogenous growth literature focuses exclusively on Cobb-Douglas. Elasticities other than unity are ignored. A recent paper by Klump and Grandville (2000) examined other elasticities but assumed an exogenous saving rate. By contrast, this paper studies elasticity and endogenous growth. Endogeneity is important since elasticity preserves capital’s productivity and encourages saving. Two models are presented. The first assumes exogenous technological change. We find elasticity to have a positive level effect on income. No rate of growth effect is found. The second model allows learning by doing from capital accumulation. In addition to the level effect, rate of growth effects are found.